Transformasi Spiritualitas: Relevansi Tasawuf dalam Kehidupan Digital Modern - Didin Solehudin; Machmud Yunus (Jurnal Shaf, 2026)
This study aims to analyze the relevance and transformation of Sufism as a spiritual paradigm in addressing the challenges of modern digital life. Using a qualitative method grounded in literature review, this study draws on primary sources from classical Sufi literature as well as secondary sources such as journals, social surveys, and contemporary digital data. Content analysis and an interpretive approach are employed to connect the core concepts of Sufism with the social realities of the digital age.  Research findings indicate a growing spiritual need among the public, reflected in high rates of stress, depression, and anxiety resulting from the intensive use of digital media. The data also shows that the younger generation is increasingly engaging in digital Sufi activities because they are perceived as relevant to their emotional and psychological needs. This study concludes that Sufism possesses the adaptive capacity to address the challenges of the digital age without losing the substance of its teachings. Values such as tazkiyatun nafs, muraqabah, and ikhlas can serve as the foundation for modern ethics and spirituality. With proper recontextualization, Sufism not only endures as a traditional heritage but becomes a functional, applicable, and solution-oriented paradigm of spiritual healing for the digital human.